Impact of entrepreneurship on university students' academic welfare during the COVID-19 pandemic in Masvingo Province, Zimbabwe - Nzwirashe Rejoyce Magomana; Msizi Mkhize; Kansilembo Freddy Aliamutu (Economics, Management and Sustainability)
The study explored how student entrepreneurship during the COVID-19 pandemic influenced academic welfare in Masvingo Province, Zimbabwe. By focusing on academic outcomes and entrepreneurial activities among university students, the study directly contributes to SDG 4: Quality Education, which promotes inclusive and equitable education, and SDG 8: Decent Work and Economic Growth, which encourages youth entrepreneurship, innovation, and sustainable employment. Qualitative research and descriptive survey design were employed to explore the aforementioned topic. The research sample was purposively sampled twenty students, seven lecturers, and two Student Affairs Division members. The research instruments that were used included questionnaires and interviews. The positive impacts established were that most students were involved in the business ventures, continued their studies, and were exposed to business ventures not offered in their curriculum. The study also revealed that some students poorly managed their time and missed lectures, resulting in psychological stress. Accordingly, it was suggested that students could employ business assistants and establish online shops to concentrate on their studies. The study recommended that universities support students through start-up funds, an inclusive timetable, and collaboration with telecommunications service providers. Students can also approach micro-financing institutions for assistance in setting up their businesses to generate funds for fees and other academic-related needs.